DIGITAL FINANCIAL LITERACY IN INDONESIA: A LITERATURE REVIEW - Putri, Arinda Mentari; Damayanti, Sylviana Maya; Rahadi, Raden Aswin (CENTRAL ASIA AND THE CAUCASUS, 2022)
Digital Era is related to the development of Financial Technology (Fintech), and the Covid-19 pandemic boost this development. With this rapid development, the phenomenon is that many people are not literate and are trapped in many lending and do investments using hot money the digital age, financial literacy has grown increasingly important, yet there is a need for something more specialized than financial literacy. Fintech development has become more reliant on digital financial literacy. However, there is currently no consensus on the definition, measurement, or characteristics that make up Digital Financial Literacy. Especially in Indonesia, level of Financial Literacy is still deficient and still large gap between Financial Literacy and Financial Inclusion. It is vital to measure Digital financial literacy to determine what dimensions of Digital Financial Literacy itself first. The methodology of this study would be using a structured literature review to determine what dimensions that would be the Digital Financial Literacy aspect. Findings from this study suggested that Digital Financial Literacy can be measured and standardized than can be evaluated each year to balance the growing of Fintech. The study would be beneficial for public, practitioners and government together facing rapid growing of Fintech with rapid growing with Digital Financial Literacy too. The uniqueness of this study is there still few studies about Digital Financial Literacy and still no standardized measurement and dimensions, so with finding this research can fill the gap. For further research we can do quantitative research to test all the dimensions for each countries.